The effect of a proposed training program using two methods (interval training and cardio exercises) to develop maximum aerobic speed in senior football players - Cherfouf, hamza; oukkal, adel (sports creativity, 2025)
The study aims to identify the impact of a proposed training program with continuous and interval circular training on the development of maximum air speed (VMA) for senior football players and for this purpose we used an experimental approach on a sample consisting of (20) players who worked with them as an experimental group, deliberately selected, then the researcher applied the codified training program for a period of (08) weeks, after which he conducted post-tests on the experimental group, and after collecting the results and processing them statistically, it was concluded that the proposed program had a moral impact on The maximum air speed of the experimental sample and on this basis, the study recommended confirming the use of the training program for the purpose of developing the maximum air speed.